A Nash-Stackelberg game approach in regional energy market considering users' integrated demand response. (15th May 2019) - Lu, Qing; Lü, Shuaikang; Leng, Yajun
Abstracts: Amid growing and progressive reform of incremental distribution business in China, the potential confrontation of the retailers and consumers has driven the necessity to study the transaction mechanism and interest equilibrium in the incremental distribution area. In this paper, a transaction mechanism among various retailers and consumers in the regional energy market is designed. And based on the characteristics of retailers and consumers, the revenue of these market participants are formulated considering consumers' satisfaction and integrated demand response (IDR). The problem is formulated as a two-leader and two-follower Nash-Stackelberg game among them, which is built with the strategy set of energy prices and consumption patterns. The proposed game is proved the existence and uniqueness of equilibrium under classical game theory, and solved by distributed algorithm through improved particle swarm optimization algorithm with constraints. Finally, an example study of the model is presented to verify the increase of revenue under the established market transaction mechanism, where the revenue of two kinds of retailers increases by 17.8% and 10.9% respectively as well as consumers' revenue increasing by 21.7% and 12.3%. In addition, sensibility analysis of the factors like compensation prices, market share of retailers and price elasticity of consumers are carried out. Highlights: The transaction mechanism in the regional energy market is designed specifically. The two-leader and two-follower Nash-Stackelberg game model is proposed. A distributed optimization algorithm is proposed to determine the game equilibrium. The reasonable compensation prices can increase the revenue of overall participants.